O Projeto De Uma Psicanálise Ontológica Em Merleau-Ponty - Severo, Daniel Cardozo [UNIFESP] (2018)
This Work Was Born When Reading A Note Written By Merleau-Ponty. This Note Was Written In December 1960 And Published In Le Visible Et L'invisible. It Is Called "Corps Et Chair " Éros - Philosophie Du Freudisme". On That Note, Merleau-Ponty Expressed The Need To Do One Psychoanalysis Ontological. This Ontological Psychoanalysis Allows Us To Deepen Our Perceptions About Being. However The Ways Taken By Merleau-Ponty To This Proposal Are Very Intricate. Many Important Elements Of The Philosopher"S Thinking Participate In This Call At The Last Gasp Of His Work. Therefore We Had To Tread These Paths To Understand The Note That Sparked Our Interest. The Research Focused On Understanding All The Elements Involved To Build A Psychoanalysis Ontological. While We Doing The Research We Perceive A Specific Use Of Merleau-Ponty Of Psychoanalysis In His Reflections. This Use Has Brought Huge Difficulties To Understand The Importance Of Psychoanalysis For Your Thoughts And The Viability Of The His Project Of To Make An Ont